Bob books. Rhyming words - Kertell, Lynn Maslen (Kertell, Lynn Maslen. Bob books., 2013)
Rhyming makes reading easier and more fun for kids that are just getting started. When rhyming words are included in a story, they make sounding out (decoding) easier. Kids have reading success sooner and faster, build confidence, and they have fun too. Bob Books Rhyming Words is a great next step after Bob Books Set 1.